Air‐Stable Conductive Polymer Ink for Printed Wearable Micro‐Supercapacitors. Issue 25 (21st May 2021) - Chu, Xiang; Chen, Guorui; Xiao, Xiao; Wang, Zixing; Yang, Tao; Xu, Zhong; Huang, Haichao; Wang, Yihan; Yan, Cheng; Chen, Ningjun; Zhang, Haitao; Yang, Weiqing; et al.
Abstract: Printed electronics are expected to facilitate the widespread distributed wearable electronics in the era of the Internet of things. However, developing cheap and stable electrode inks remains a significant challenge in the printed electronics industry and academic community. Here, overcoming the weak hydrophilicity of polyaniline, a low‐cost, easy‐fabricating, and air‐stable conducting polymer (CP) ink is devised through a facile assemble‐disperse strategy delivering a high conductivity in the order of 10 −2 S cm −1 along with a remarkable specific capacitance of 386.9 F g −1 at 0.5 A g −1 (dehydrated state). The additive‐free CP ink is directly employed to print wearable micro‐supercapacitors (MSCs) via the spray‐coating method, which deliver a high areal capacitance (96.6 mF cm −2 ) and volumetric capacitance (26.0 F cm −3 ), outperforming most state‐of‐the‐art CP‐based supercapacitors. This work paves a new approach for achieving scalable MSCs, thus rendering a cost‐effective, environmentally friendly, and pervasive energy solution for next‐generation distributed electronics. Abstract : A low‐cost, scalable, and air‐stable conducting polymer ink is invented via a facile assemble‐disperse strategy for printed micro‐supercapacitors, which exhibits remarkable energy storage capacity as a power source for wearable bioelectronics in the era of Internet of things.